2017
DOI: 10.1242/jeb.145623
|View full text |Cite
|
Sign up to set email alerts
|

Archer fish jumping prey capture: kinematics and hydrodynamics

Abstract: Smallscale archer fish, Toxotes microlepis, are best known for spitting jets of water to capture prey, but also hunt by jumping out of the water to heights of up to 2.5 body lengths. In this study, high-speed imaging and particle image velocimetry were used to characterize the kinematics and hydrodynamics of this jumping behavior. Jumping used a set of kinematics distinct from those of in-water feeding strikes and was segmented into three phases: (1) hovering to sight prey at the surface, (2) rapid upward thru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…While jumping may reduce the threat of kleptoparasitism, it only works for prey that are close to the water surface as archerfish are unable to jump as high as they can effectively shoot (Shih, Mendelson, & Techet, 2017). In situations where an archerfish must shoot, nearby conspecifics are likely to affect the decision making of the shooting fish.…”
Section: Introductionmentioning
confidence: 99%
“…While jumping may reduce the threat of kleptoparasitism, it only works for prey that are close to the water surface as archerfish are unable to jump as high as they can effectively shoot (Shih, Mendelson, & Techet, 2017). In situations where an archerfish must shoot, nearby conspecifics are likely to affect the decision making of the shooting fish.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at animals larger than the capillary length scale, a small fish like the Trinidadian guppy can jump around 3.5 body lengths [7]. A detailed analysis of the archerfish kinematics show they can jump around 2.5 body lengths [29]. While the caudal fin appears to produce the most thrust, this study also showed the importance of the anal, pectoral and dorsal fins during thrust production using particle image velocimetry.…”
Section: Introductionmentioning
confidence: 60%
“…Rossel et al, 2002;Reinel and Schuster, 2018a). Jumping, per se, is more costly and can be used only at low target height, but it can secure prey with no further investment needed and at overall costs that are comparable to shooting plus subsequent retrieval (Shih et al, 2017). When jumping, the fish position themselves directly below their prey (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When jumping, the fish position themselves directly below their prey (e.g. Shih et al, 2017), but when shooting, they take more lateral positions (e.g. Timmermans, 2001;Rossel et al, 2002;Schuster et al, 2004).…”
Section: Introductionmentioning
confidence: 99%